2015
DOI: 10.1016/j.bbadis.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NADPH oxidase mediates increased endoplasmic reticulum stress and left ventricular remodeling after myocardial infarction in rabbits

Abstract: Nicotinamide adenine dinucleotide 3-phosphate (NADPH) oxidase activity and endoplasmic reticulum (ER) stress are increased after myocardial infarction (MI). In this study, we proposed to test whether activation of the NADPH oxidase in the remote non-infarcted myocardium mediates ER stress and left ventricular (LV) remodeling after MI. Rabbits with MI or sham operation were randomly assigned to orally receive an NADPH oxidase inhibitor apocynin or placebo for 30 days. The agents were administered beginning at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
1
40
0
1
Order By: Relevance
“…Luo et al [110] reported that MI induced ERS and provoked cardiac apoptosis and fibrosis by increasing the expression of ERS markers GRP78 and CHOP, pro-apoptotic proteins Bax and caspase 3, and pro-fibrotic proteins transforming growth factor-beta 1 (TGF-β1) and Smad 2/3, culminating in cardiac rupture and remodeling. Li et al [111] reported that ERS contributed to MI through the activation of NADPH oxidase. NADPH oxidase inhibition attenuated an increase in ERS in the remote non-infarcted myocardium and LV remodeling after MI by preventing the increase of GRP78, CHOP and cleaved caspase 12 protein expression in rabbits.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…Luo et al [110] reported that MI induced ERS and provoked cardiac apoptosis and fibrosis by increasing the expression of ERS markers GRP78 and CHOP, pro-apoptotic proteins Bax and caspase 3, and pro-fibrotic proteins transforming growth factor-beta 1 (TGF-β1) and Smad 2/3, culminating in cardiac rupture and remodeling. Li et al [111] reported that ERS contributed to MI through the activation of NADPH oxidase. NADPH oxidase inhibition attenuated an increase in ERS in the remote non-infarcted myocardium and LV remodeling after MI by preventing the increase of GRP78, CHOP and cleaved caspase 12 protein expression in rabbits.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…Healthy adult male New Zealand White rabbits (2-2.5 kg) obtained from the Academy of Military Medical Sciences were prepared for MI produced by coronary artery ligation as described before [13]. The rabbits were anesthetized by intraperitoneal injection of pentobarbital sodium (50mg/kg) and mechanically ventilated with a respirator (HX-101E, Taimeng Technology Co., Ltd., Chengdu, China).…”
Section: Animal Model and Experimental Protocolmentioning
confidence: 99%
“…The H9C2 rat cardiomyocyte line was obtained from the Chinese Academy of Sciences Cell Bank (Shanghai, China; The American Type Culture Collection, Manassas, VA, USA) [13]. The H9C2 cardiomyocytes were cultured in 25 cm 2 flask in Dulbecco's modified Earle's medium (DMEM) (Gibco, Life Technologies, USA) with 3.7 g/L sodium bicarbonate, 4.5 g/L D-glucose, and 110 mg/L sodium pyruvate, supplemented with 10% fetal bovine serum (Australia) and penicillin (100 units/mL) and streptomycin (100 μg/mL) in a humidified incubator with 95% air and 5% CO 2 at 37 °C.…”
Section: H9c2 Cardiomyocyte Culture and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations